2018
DOI: 10.1002/1873-3468.13294
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite systems profiling identifies exploitable weaknesses in retinoblastoma

Abstract: Retinoblastoma (RB) is a childhood eye cancer. Currently, chemotherapy, local therapy, and enucleation are the main ways in which these tumors are managed. The present work is the first study that uses constraint‐based reconstruction and analysis approaches to identify and explain RB‐specific survival strategies, which are RB tumor specific. Importantly, our model‐specific secretion profile is also found in RB1‐depleted human retinal cells in vitro and suggests that novel biomarkers involved in lipid metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 92 publications
5
14
1
Order By: Relevance
“…We found that advanced Rb was associated with a low expression of glycolytic genes and altered Krebs cycle with a higher propensity for fatty acid metabolism. Our findings are also supported by a recent study that highlighted the role of lipid metabolism in Rb tumors [45]. Furthermore, our global metabolomic profiling of Rb vitreous humor identified a variety of differentially accumulated metabolites that are distinct from the pediatric controls.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that advanced Rb was associated with a low expression of glycolytic genes and altered Krebs cycle with a higher propensity for fatty acid metabolism. Our findings are also supported by a recent study that highlighted the role of lipid metabolism in Rb tumors [45]. Furthermore, our global metabolomic profiling of Rb vitreous humor identified a variety of differentially accumulated metabolites that are distinct from the pediatric controls.…”
Section: Discussionsupporting
confidence: 87%
“…This integrated omics analysis of the Rb tumor transcriptome and the vitreous humor metabolome within the human Rb tumor subtypes using the pediatric retina as controls was performed to enrich our understanding of altered gene function with changes in tumor metabolism. Although there have recently been a few reports on alterations in the Rb tumor-associated metabolites [45,46], we found significantly more functional associations between the metabolic targets and the enriched pathways owing to the coordinated samples used for analysis and the use of age-matched pediatric controls. Although we have focused on intraocular advanced and non-advanced retinoblastoma tumors, our findings can be extended to other cancer systems with persistent RB1 mutations.…”
Section: Discussioncontrasting
confidence: 57%
“…It is involved in retinal maturation and development [ 80 ]. It has been shown that most Rb tumours are able to generate endogenous GABA via one or several different biosynthetic pathways [ 81 ]. Importantly, GABA is related to cancer cell metastasis and proliferation [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, many more cancer-specific models have been reconstructed for liver ( 106 , 149 , 155 , 166 , 173 , 181 ), kidney ( 152 , 154 , 162 , 172 , 172 ), breast ( 103 , 105 , 131 , 145 , 168 ), prostate ( 103 , 104 , 157 , 161 , 162 , 175 ), brain ( 103 , 153 , 167 ), colorectal ( 159 , 170 , 192 ), head and neck ( 148 ), eye ( 147 ), and lung ( 103 , 105 , 131 , 175 ) cancer to generate cancer-specific hypotheses. To compare these various methods for reconstruction of cancer metabolic models, a study benchmarked their predictive performance and consistency ( 91 ), with relevant findings summarized in Table 2 .…”
Section: Genome-scale Modeling Of Cancer Metabolism With Cobra Toolsmentioning
confidence: 99%